Continuous particle separation using pressure-driven flow-induced miniaturizing free-flow electrophoresis (PDF-induced μ-FFE) - Jeon, Hyungkook (Sci Rep, 2016)
In this paper, we introduce pressure-driven flow-induced miniaturizing free-flow electrophoresis (PDF-induced μ-FFE), a novel continuous separation method. In our separation system, the external flow and electric field are applied to particles, such that particle movement is affected by pressure-driven flow, electroosmosis, and electrophoresis. We then analyzed the hydrodynamic drag force and electrophoretic force applied to the particles in opposite directions. Based on this analysis, micro- and nano-sized particles were separated according to their electrophoretic mobilities with high separation efficiency. Because the separation can be achieved in a simple T-shaped microchannel, without the use of internal electrodes, it offers the advantages of low-cost, simple device fabrication and bubble-free operation, compared with conventional μ-FFE methods. Therefore, we expect the proposed separation method to have a wide range of filtering/separation applications in biochemical analysis.